Self-consistent approach for modeling coupled elastic and visco-plastic processes induced by dislocation and pressure solution. (1st March 2022) - Xu, Tingting; Arson, Chloé
Abstract: This paper presents a self-consistent approach in which coupled non-linear time-dependent deformation mechanisms are estimated by an affine approximation and elastic and visco-plastic macroscopic properties are calculated for the most general form of anisotropy. Phase changes from crystal to pore are accounted for, via a grain breakage mechanism. As an example, we study dislocation and pressure solution, two non-linear deformation mechanisms common to a wide range of polycrystalline materials. To this date, the couplings between the two are not fully understood. We analyze the sensitivity of the behavior of halite polycrystals to stress, brine content, grain size and grain breakage. Results indicate that: Pressure solution yields mechanical healing only if grain breakage is ignored; Otherwise, pressure solution accelerates dislocation creep, which results in an abrupt increase of elastic and viscoplastic compliance components; Higher stress and/or higher brine content enhance the coupled effects of pressure solution and dislocation; Pressure solution is delayed by the occurrence of larger grains and by the entrapment of fluid in isolated pores. An interesting feature of the model is the representation of the pore space, which allows distinguishing the deformation mechanisms of these isolated pores from those of the pores where precipitation occurs.